WACANA POLITIK KEAGAMAAN DALAM NOVEL CHINMOKU KARYA SHUSAKU ENDO - Dian Pramita Sugiarti (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2013)
This study concerns the interpretation of religious political discourse in the work of Shusaku Endo's novel Chinmoku. Formulation of the problem is expressed in the form of the following questions (1) how to shape political discourse in the novel Chinmoku religious? 2) in the context of whether religious political discourse delivered? (3) What is the meaning of religious political discourse in the novel Chinmoku? This study aims to (1) enriches the study of literature, especially Japanese Literature was the historical background of the 17th century (2) describe historical facts about Japan in the late 17th century as outlined in the novel Chinmoku. This study was designed as a qualitative analysis based on religious political discourse in the novel Chinmoku. This study will be analyzed using sociological theory and literary hegemony, to analyze the condition of the people of Japan as a result of the prohibition of the spread of Christianity is considered a threat to overthrow the regime of the Japanese government. Another result of this study is the presence of religious political issues that exist in the spread of Christianity in Japan for certain purposes. In Christian teaching contained political manipulation that want to master Japanese, and compete with religions existing in Japan the Shinto, Buddhist and Kon Fu Tsu.